2020
DOI: 10.2139/ssrn.3638328
|View full text |Cite
|
Sign up to set email alerts
|

Capital Flows-at-Risk: Push, Pull and the Role of Policy

Abstract: We characterise the probability distribution of capital flows for a panel of emerging market economies conditional on information contained in financial asset prices, with a focus on 'tail' events. Our framework, based on the quantile regression methodology, allows for a separate role of push and pull-type factors, and offers insights into the term-structure of these effects. We find that both push and pull factors have heterogeneous effects across the distribution of capital flows, with the strongest reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…Earlier work focused on "disaster risk" and extreme negative tail events (such as Barro, 2009;Gabaix, 2012;Wachter, 2013;and Gourio, 2012) and more recent work has built on the "growth at risk" framework developed in Adrian et al (2019). Gelos et al (2019), Eguren-Martin et al (2020, and Mano and Sgherri (2020) adopt the quantile regression framework used in this literature to estimate the impact of push and pull shocks (including risk shocks) on future quarterly capital flows in emerging markets. These papers find significant effects of these shocks on different parts of the capital flow distribution, especially on the tails.…”
Section: Previous Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Earlier work focused on "disaster risk" and extreme negative tail events (such as Barro, 2009;Gabaix, 2012;Wachter, 2013;and Gourio, 2012) and more recent work has built on the "growth at risk" framework developed in Adrian et al (2019). Gelos et al (2019), Eguren-Martin et al (2020, and Mano and Sgherri (2020) adopt the quantile regression framework used in this literature to estimate the impact of push and pull shocks (including risk shocks) on future quarterly capital flows in emerging markets. These papers find significant effects of these shocks on different parts of the capital flow distribution, especially on the tails.…”
Section: Previous Literaturementioning
confidence: 99%
“…These papers also include some analysis of how various policies can moderate the impact of these shocks, but most find little impact of macroprudential regulations on the future distribution of capital flows. The one exception is Eguren-Martin et al (2020), which finds evidence that tightening macroprudential policy can reduce the impact of push factors on capital flows-at-risk at the extremes. The proxies for macroprudential regulations in these papers are blunt, however, with dummy variables capturing any recent changes in any type of macroprudential policy.…”
Section: Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Outflows were large, even when factoring in the deterioration in financial market conditions. Using a framework that allows us to model the entire distribution of non-resident capital flows to EMEs as a function of prevailing (price-based) financial conditions that distinguish between push-and pull-type drivers of capital flows (Eguren Martin et al, 2020 andCarney, 2019), we see that the magnitude of portfolio outflows observed in March, April and May (as a share of quarterly GDP) was a very low probability event, even when taking into account the deterioration in financial conditions observed during March (Chart 4). The probability of observing such large outflows was just 12%.…”
Section: Magnitudementioning
confidence: 99%
“…Ex-post, the easing of MPMs can help absorb the shocks. MPMs may also contribute to reduce the sensitivity of capital flows to global factors and reduce the likelihood of sudden stops(Eguren Martin et al, 2020). Most countries in our sample eased MPMs, mainly by relaxing capital and liquidity buffers countercyclically, in order to support credit and preserve the viability of domestic banks.…”
mentioning
confidence: 97%